Plasmon Hybridization-Induced Ultra-broadband High Absorption from 0.4 to 1.8 Microns in Titanium Nitride Metastructures - Wu, Shiwen; Luo, Tengfei; Xiong, Guoping (Plasmonics (Norwell, Mass.), 2021)
Titanium nitride (TiN) metadevices as perfect absorbers are studied using finite-difference time-domain (FDTD) simulations. In this paper, we demonstrate a metastructure including a top silica (SiO 2 ) layer, two layers of TiN nano-ribbon arrays, a SiO 2 dielectric layer, and a TiN film to realize efficient solar energy harvesting. We theoretically optimize the geometrical parameters of each active layer to achieve high absorption rates with an average value of up to 95% within an ultra-wide band from 0.4 to 1.8 microns, covering over 93% of total energy in the solar spectrum. Our detailed analysis of the electric field enhancement indicates that such ultra-broadband high absorption in the visible/near-infrared ranges can be attributed to surface plasmon resonances, Fabry-Perot resonances, and strong plasmon hybridization between adjacent TiN nano-ribbons. Together with refractory properties of TiN and SiO 2 , the designed metadevice may exhibit great potential in efficient solar energy harvesting applications, particularly in harsh environments.